1994
DOI: 10.1063/1.356629
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscope stimulated oxidation of silicon (100) surfaces

Abstract: The chemical modification of n- and p-type hydrogen-passivated Si(100) surfaces by a scanning tunneling microscope (STM) is reported. The modified areas have been examined with STM, Auger electron spectroscopy, scanning electron microscopy, and atomic force microscopy. Comparison of these characterization techniques indicates the features are both chemical and topographic in nature and are the result of local oxidation of the substrate. In addition, pattern transfer for the defined regions has been demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] For pattern transfer, the oxidized regions can either be removed in selective etching solutions 2,7 or act as robust etching masks. 3,4,8 Exposure of H-terminated Si surfaces to tipemitted electrons in an ultrahigh-vacuum environment entails a selective desorption of passivated hydrogen, converting the surface locally into highly reactive regions. [9][10][11][12] Dosing experiments with O 2 ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] For pattern transfer, the oxidized regions can either be removed in selective etching solutions 2,7 or act as robust etching masks. 3,4,8 Exposure of H-terminated Si surfaces to tipemitted electrons in an ultrahigh-vacuum environment entails a selective desorption of passivated hydrogen, converting the surface locally into highly reactive regions. [9][10][11][12] Dosing experiments with O 2 ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…2b. This behavior has been reported before for modifications produced at positive sample voltages [8] and it can be explained if we assume that the surface is oxidized: the apparent depression shown in the STM image is due to a change of conductivity of the surface and to the fact that silicon is consumed to produce silicon oxide. The change of the conductivity of the surface is also observed if tunneling current versus sample voltage (I/V ) curves are performed on the modified areas.…”
Section: Experiments Performed In Airmentioning
confidence: 75%
“…In addition, breakthroughs towards the practical application of the technique were introduced in 1993 by Day and Allee [6], who used AFM with a metallized tip instead of STM to oxidize silicon surfaces locally, and by Snow et al [7], who locally oxidized H-passivated silicon surfaces using AFM. Other relevant results that should be mentioned are those of Fay et al [8], who demonstrated that the STM-oxidized regions appear as depressed areas when imaged with STM but as raised areas when imaged with AFM, and the dependence of the oxidation on the air humidity as * Corresponding author found by several authors [9]. It has also been demonstrated that photons from the probe of a scanning near-field optical microscope (SNOM) induce local oxidation of an amorphous Si-H film [10].…”
mentioning
confidence: 90%
“…As usual, the Si surface modification obtained during STMmeasurements is explained by the irreversible oxidation [1][2][3][4]6,7]. The layer of adsorbate molecules is considered to assist with the oxidation.…”
Section: Si-sio 2 -Polymer System: Surface Modificationmentioning
confidence: 99%
“…The results of some works showed a possibility for the silicon surface to be modified during the STM study in air [1][2][3][4]. The explanation of this fact was in the oxidation process on the Si-surface near the place of a flowing current.…”
Section: Introductionmentioning
confidence: 99%